2023
DOI: 10.1007/s00701-023-05570-1
|View full text |Cite
|
Sign up to set email alerts
|

Artificial cerebrospinal fluid use during burr-hole surgery and reoperation rate in patients with chronic subdural hematoma: an analysis using a nationwide inpatient database

Abstract: Background The optimal surgical procedure to reduce the recurrence rate of chronic subdural hematoma (CSDH) after burr-hole surgery remains to be established. This study aimed to investigate the association between artificial cerebrospinal fluid (ACF) use during burr-hole surgery and reoperation rate in patients with CSDH. Method In this retrospective cohort study, we used the Japanese Diagnostic Procedure Combination inpatient database. We identified pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…After removing 594 duplicates, we screened the remaining 943 publications based on article type, title, and abstracts and excluded 936 unrelated publications, leaving seven studies. We meticulously evaluated the seven publications for potential eligibility (12,15,16,21,(29)(30)(31), and all met inclusion criteria. Subsequently, we manually searched the Chinese database for relevant studies and found four additional studies (32)(33)(34)(35) that met our inclusion criteria.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing 594 duplicates, we screened the remaining 943 publications based on article type, title, and abstracts and excluded 936 unrelated publications, leaving seven studies. We meticulously evaluated the seven publications for potential eligibility (12,15,16,21,(29)(30)(31), and all met inclusion criteria. Subsequently, we manually searched the Chinese database for relevant studies and found four additional studies (32)(33)(34)(35) that met our inclusion criteria.…”
Section: Study Selectionmentioning
confidence: 99%
“…Subsequently, we manually searched the Chinese database for relevant studies and found four additional studies (32)(33)(34)(35) that met our inclusion criteria. In summary, we included a total of 11 studies (12,15,16,21,(29)(30)(31)(32)(33)(34)(35) in our systematic review and meta-analysis (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations